Ensino de Ciências e conhecimento pedagógico de conteúdo: narrativas e práticas de professoras da séries iniciais. - Ely Roberto da Costa Maues (2003)
This paper analyzes the strategies by elementary school Science teachers of grades 1st-4th. Bassed on the analytical approach of Lee Schulman (1987) of Pedagogical Content Knowledge(PCK), this research sought to understand the relation between content knowledge and pedagogical knowledge in the teaching-learning practices of Science teachers of the 1st-4th grades. Previous research based on the PCK analytical viewpoint indicated that the knowledge of contents would be practically the only pre- requisite for the development of PCK. Our field research with 09 teachers of grades 1st-4th of 2002 indicates a more dialectic relation between content knowledge and PCK. Despite a precarious Science content knowledge, the teachers interviewed revealed a great creativity in the use of teaching strategies. The use of a general PCK applicable to the areas of Mathematics, Portuguese, Arts and Science in the first grads have not been properly acknowledged by previous research, and a more appropriate approach of the situation of Science teaching in the first grades is called for.